2021
DOI: 10.1055/s-0041-1726034
|View full text |Cite
|
Sign up to set email alerts
|

Different Anticoagulant Regimens, Mortality, and Bleeding in Hospitalized Patients with COVID-19: A Systematic Review and an Updated Meta-Analysis

Abstract: We conducted a systematic review and a meta-analysis to assess the association of anticoagulants and their dosage with in-hospital all-cause mortality in COVID-19 patients. Articles were retrieved until January 8, 2021, by searching in seven electronic databases. The main outcome was all-cause mortality occurred during hospitalization. Data were combined using the general variance-based method on the effect estimate for each study. Separate meta-analyses according to type of COVID-19 patients (hospitalized or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 57 publications
(318 reference statements)
4
59
2
1
Order By: Relevance
“…Two relevant meta-analyses have been identified through our literature search [ 46 , 47 ]. Both of them analyzed studies comparing the efficacy and safety of therapeutic versus prophylactic dose of thromboprophylaxis and confirmed a trend towards clinical benefits of therapeutic dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two relevant meta-analyses have been identified through our literature search [ 46 , 47 ]. Both of them analyzed studies comparing the efficacy and safety of therapeutic versus prophylactic dose of thromboprophylaxis and confirmed a trend towards clinical benefits of therapeutic dose.…”
Section: Discussionmentioning
confidence: 99%
“…Both of them analyzed studies comparing the efficacy and safety of therapeutic versus prophylactic dose of thromboprophylaxis and confirmed a trend towards clinical benefits of therapeutic dose. However, mixed adjusted and unadjusted estimates were used, rendering these analyses inconclusive [ 46 , 47 ]. In the present meta-analysis, only high-quality studies with adjusted effect size estimates were included.…”
Section: Discussionmentioning
confidence: 99%
“… Drug No. patients Dose Outcome Effect Ivermectin ( AFMZ et al, 2021 ) 1,788 140 - 400 µg/kg Mortality reduction RR = 0.39 (95% CI: 0.20 - 0.74); p = 0.004 Colchicine ( Golpour et al, 2021 ) 5,901 NA Mortality reduction RR = 0.644 (95% CI: 0.555 – 0.748) Niclosamide ( Abdulamir et al, 2021a ) 150 3 g per day Reduced recovery time p ≤ 0.05 Tofacitinib ( Gunay et al, 2021 ) 289 10 mg twice a day Mortality reduction HR = 0.49 (95% CI: 0.15 to 1.63) Bamlanivimab - Etesevimab ( Dougan et al, 2021 ) 1,035 2.8 g + 2.8 g Hospitalizations or death absolute risk difference = −4.8%; (95% CI − 7.4 - −2.3); RR = 0.3; p < 0.001 Bamlanivimab - Etesevimab ( Gottlieb et al, 2021 ) 577 2.8 g + 2.8 g Viral load Viral load change = - 0.57 (95% CI: −1.00 to −0.14); p = 0.01 Anticoagulants ( Parisi et al, 2021 ) 25,719 therapeutic and prophylactic dose Mortality reduction RR = 0.50 (95% CI: 0.40 - 0.62) ASA ( RECOVERY Collaborative Group, 2021 ) 14,892 150 mg Mortality reduction RR = 0.96 (95% CI 0.89 – 1.04); p = 0.35 …”
Section: Other Agents Tested For Potential Efficacy In Treating Covid-19 Infectionmentioning
confidence: 99%
“…In addition to these limitations, the risk of bleeding should be assessed on an individualized and continuous basis, especially if higher rather than standard thromboprophylaxis doses are administered, since they are associated with a higher incidence of bleeding [41,42]. A meta-analysis involving 7781 patients hospitalized for COVID-19 showed that standard doses of thromboprophylaxis were not associated with an excess of bleeding compared to no thromboprophylaxis, while the use of therapeutic anticoagulation was associated with more than two-fold increased risk of bleeding than standard thromboprophylaxis [41]. This excess of bleeding events needs to be weighed against any potential benefit of therapeutic anticoagulant doses as a part of COVID-19 treatment.…”
Section: Discussionmentioning
confidence: 99%